Ash fusion characteristics of bamboo, wood and coal. (15th October 2018) - Liu, Zhijia; Zhang, Tao; Zhang, Jian; Xiang, Hongzhong; Yang, Xiaomeng; Hu, Wanhe; Liang, Fang; Mi, Bingbing
Abstract: Ash fusion characteristics of bamboo, masson pine and coal were investigated using X-ray fluorescence (XRF), X-ray diffraction (XRD), scanning electron microscopy (SEM) and transmission electron microscopy (TEM). XRF results showed that the major components of bamboo ash were K2 O, SiO2 and SO3 . Masson pine ash mainly included Fe2 O3 and CaO. Coal ash was comprised of SiO2, Al2 O3, CaO, Fe2 O3 and SO3 . The variation of major components resulted in different fusion characteristics, such as the low fusion temperature of bamboo ash and the high thermal conductivity of masson pine ash. XRD results confirmed chemical compositions transformation because six main chemical reactions occurred during thermal treatment process. SEM and TEM results showed that the elongated grains or plates of various sizes of all thermal treated ashes disappeared and they had less pores and denser structure on the surface, indicating structure transformation. The results from this research will be helpful to promote utilization of masson pine and bamboo for fuel in power station of China. Highlights: Each ashes have different major components. Bamboo ash has the lowest fusion temperature. There are six chemical reactions during tranformation process. The elongated grains or plates of treated ashes disappear. Treated ashes have less pores and denser structure.